Guideline concordant detection and management of depression among Alaska Native and American Indian people in primary care - Vanessa Y. Hiratsuka; Julia J. Smith; Sara M. Norman; Spero M. Manson; Denise A. Dillard (International Journal of Circumpolar Health, 2015)
Background: A tribal health organization in Alaska implemented a primary care depression screening, detection and management initiative amongst 55,000 Alaska Native/American Indian people (AN/AIs). Objectives: (a) To describe the proportion of AN/AIs screening positive for depression with depression noted or diagnosed and proportion with guideline concordant management and (b) to assess whether management varied by patient and provider factors. Research design: Secondary analysis of electronic and paper medical record information of 400 AN/AIs. Measures: Provider variables, patient demographics and patient clinical factors were electronically queried. Manual chart audits assessed depression notation, diagnoses and management within 12 weeks of positive screening. Multilevel ordinal logistic modelling assessed management by patient and provider factors. Results: A depression diagnosis was present in 141 (35%) charts and 151 (38%) had depressive symptoms noted. Detection was higher among AN/AIs with moderate and severe depression (p<0.001). In total, 258 patients (66%) received guideline concordant management, 32 (8%) had some management, and 110 (28%) received no management. Younger patient age and increased provider tenure increased odds of management. Conclusions: Most AN/AIs screening positive for depression received initial guideline concordant management. Additional outreach to older patients and additional support for providers newer to practices appears warranted.